Chloroplast nucleoids are highly dynamic in ploidy, number, and structure during angiosperm leaf development. (5th February 2020) - Greiner, Stephan; Golczyk, Hieronim; Malinova, Irina; Pellizzer, Tommaso; Bock, Ralph; Börner, Thomas; Herrmann, Reinhold G.
Summary: Chloroplast nucleoids are large, compact nucleoprotein structures containing multiple copies of the plastid genome. Studies on structural and quantitative changes of plastid DNA (ptDNA) during leaf development are scarce and have produced controversial data. We have systematically investigated nucleoid dynamics and ptDNA quantities in the mesophyll of Arabidopsis, tobacco, sugar beet, and maize from the early post‐meristematic stage until necrosis. DNA of individual nucleoids was quantified by DAPI‐based supersensitive epifluorescence microscopy. Nucleoids occurred in scattered, stacked, or ring‐shaped arrangements and in recurring patterns during leaf development that was remarkably similar between the species studied. Nucleoids per organelle varied from a few in meristematic plastids to >30 in mature chloroplasts (corresponding to about 20–750 nucleoids per cell). Nucleoid ploidies ranged from haploid to >20‐fold even within individual organelles, with average values between 2.6‐fold and 6.7‐fold and little changes during leaf development. DNA quantities per organelle increased gradually from about a dozen plastome copies in tiny plastids of apex cells to 70–130 copies in chloroplasts of about 7 μm diameter in mature mesophyll tissue, and from about 80 plastome copies in meristematic cells to 2600–3300 copies in mature diploid mesophyll cells without conspicuous decline during leaf development. Pulsed‐field electrophoresis, restriction of high‐molecular‐weight DNA from chloroplasts and gerontoplasts, and CsCl equilibrium centrifugation of single‐stranded and double‐stranded ptDNA revealed no noticeable fragmentation of the organelle DNA during leaf development, implying that plastid genomes in mesophyll tissues are remarkably stable until senescence. Significance Statement: Plastid DNA is organized in nucleoids that are highly dynamic in organization, structure, number, and DNA amount during leaf development. The present investigation now fully resolves this dynamic and is a precise cytogenetic and quantitative characterization of nucleoid DNA in the mesophyll spanning the entire life cycle of the leaf.